Building state centrality through state selective financialization: Reconfiguring the land reserve system in China. - Feng, Yi; Wu, Fulong; Zhang, Fangzhu (Environment & Planning A, 2024)
The state has been pivotal in both facilitating financialization and dealing with its consequences, through which the state itself has also been reshaped. This paper proposes a "state selective financialization" framework to highlight the intentionality and selectivity of the state in (de)financialization. Based on practices in China, we examine the latest state efforts to reconfigure the land reserve system in order to cope with local financial risks associated with land-backed borrowing. The state de-leverages reserved land locally and uses it to secure bonds through a state-managed top-down process. The changing mechanism demonstrates the central state's intentional role in selecting financial instruments and recentralizing its control over land financialization, whereby it has tried to mitigate financial risks and oversee local development. Instead of financialization versus de-financialization, we find financialization in China is a selective governance tactic to address state concerns. Moreover, rather than seeing financialization as a process outside the state, this research emphasizes that selective financialization is an internal process to reconsolidate the power of the central state and rebuild alignment among multi-scalar state actors.